2014
DOI: 10.12806/v13/i1/r1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Civic Engagement in Undergraduate Leadership Courses

Abstract: Undergraduate leadership courses are becoming increasingly important venues to promote civic engagement. Despite their prominence, the nature of civic engagement in leadership courses has not been examined systematically. This study examined 77 introductory undergraduate leadership courses and the role of civic engagement in these courses. Results indicate that civic engagement components are not widely utilized, and when they are part of the curricula, their implementation and design vary. Recommendations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…With regard to pre-college activities and leader emergence, our findings noted that students who participated in community service/volunteering, extracurriculars, and peer tutoring pre-college were more likely to engage in leadership activities during college. This discovery supports previous studies, which have shown civic engagement to be a powerful driver for leadership development (e.g., Johnson & Woodard, 2014). Our results also highlight that pre-college participation in extracurriculars, such as camps and academies, can influence leadership development (Bates et al, 2019) and underscore the leadership connection to peer tutoring (e.g., Hogan, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…With regard to pre-college activities and leader emergence, our findings noted that students who participated in community service/volunteering, extracurriculars, and peer tutoring pre-college were more likely to engage in leadership activities during college. This discovery supports previous studies, which have shown civic engagement to be a powerful driver for leadership development (e.g., Johnson & Woodard, 2014). Our results also highlight that pre-college participation in extracurriculars, such as camps and academies, can influence leadership development (Bates et al, 2019) and underscore the leadership connection to peer tutoring (e.g., Hogan, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…In conclusion, we echo Johnson and Woodard's (2014) challenge to further explore leadership education's role in fulfilling higher education's civic mission. Through servicelearning, leadership educators can create a learning environment that challenges students to not only consider social challenges, but apply leadership for the common good through civic engagement.…”
Section: Reflection and Recommendationsmentioning
confidence: 84%
“…However, Johnson and Woodard's (2014) review of introductory leadership curricula identified a need to strengthen the intersections between leadership education and civic engagement. Of the 77 leadership course syllabi they studied, only about one quarter of them included a civic component (Johnson & Woodard, 2014). Although servicelearning has been documented as a source of learning used in student leadership development (Allen & Hartman, 2009), Jenkins (2012) reported that out of a sample of 303 leadership educators, only 11.2% (n = 34) identified service-learning as one of their "top three" most used instructional strategies (p. 13).…”
Section: Introductionmentioning
confidence: 99%
“…Leadership education programs assist in the development of leaders who make change in their national and international communities. Civic learning and engagement can be the catalyst for student learning in leadership development and education programs across the country (Brungardt, Greenleaf, Brungardt, & Arensdorf, ; Council for the Advancement of Standards in Higher Education (CAS), , ; Johnson & Woodard, ).…”
Section: Introductionmentioning
confidence: 99%